Implementation of Tree Diagram Method, Failure Mode Effect Analysis (FMEA) and 5W 1H to Reduce Corky Defective Products in PT. XYZ - Mohamad Solihudin; Wakhid Nurhidayat; Suwandi Suwandi; Candra Setia Bakti; Rachmat Rachmat; Agus Hari Hadi; Sapta Nugroho (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT XYZ is a company that manufactures of tire fabrics in the Tangerang. Global competition force the company continues to strive to reduce process costs, one of which is by reducing the highest percentage of defects, namely corky defects, corky defects reach 39.7% of total defects. The tree diagram and FMEA methods, selected for the analysis of potential failures that cause corky defects are found namely: Threads are not clamped when changing pots, joints are not pulled at the beginning of running, roll regulator worn is used for the process, dirty of roll regulator is used for the process, wrong setting inner brake. The 5W 1H method results from corrective actions, namely: Refreshing programs for twisting production operators, checking periodically the roll regulator used by the process is still good, making schedules, and reporting on the implementation of cleaning roll regulators and evaluating by production leaders. From the corrective actions taken, it succeeded in reducing the percentage of corky defects in the twisting plant 2 process, down from 39.7% to 14.9% in semester 2 of 2021.